2013
DOI: 10.1155/2013/324329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infection among HIV Positive Persons Who Are Naive and on Antiretroviral Treatment in Hiwot Fana Specialized University Hospital, Eastern Ethiopia

Abstract: Background. Intestinal parasitic infection affects the health and quality of life of people living with HIV. This study was aimed to determine the prevalence of intestinal parasites among HIV positive individuals who are naive and who are on antiretroviral treatment (ART) in Hiwot Fana Specialized University Hospital, Eastern Ethiopia. Methods. A comparative cross-sectional study was conducted on 371 (112 ART-naive group and 259 on ART) HIV positive individuals. Stool specimens were collected and examined by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 16 publications
11
39
5
2
Order By: Relevance
“…Some studies reported that the improved immune system could reduce Blastocystis infection among HIV-infected children who were on antiretroviral treatment when compared with those who did not receive the antiretroviral therapy. 27,28 In our study, the prevalence of Blastocystis infection among HIV-infected children was significantly lower than among those HIV negatives, which was consistent with other studies from China 29 and Tanzania. 30,31 There is no evidence that either antiretroviral drugs or co-trimoxazole can prevent Blastocystis infection.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies reported that the improved immune system could reduce Blastocystis infection among HIV-infected children who were on antiretroviral treatment when compared with those who did not receive the antiretroviral therapy. 27,28 In our study, the prevalence of Blastocystis infection among HIV-infected children was significantly lower than among those HIV negatives, which was consistent with other studies from China 29 and Tanzania. 30,31 There is no evidence that either antiretroviral drugs or co-trimoxazole can prevent Blastocystis infection.…”
Section: Discussionsupporting
confidence: 92%
“…The overall prevalence of intestinal parasite infections in pre ART and on ART patients were 53.7% and 36.8%, respectively which is higher than a study conducted in Dessie hospital with prevalence of IP infections 39% for pre ART patients and 17.6% for on ART patients [13] and higher than a study conducted in Eastern Ethiopia, Hiwot Fana specialized hospital with prevalence of 45.5% for pre-ART patients and 33.7 % for on ART patients [14]. This may be due to differences in geographic locations and difference in study participants since this study was conducted in rural woreda which may cause the high prevalence.…”
Section: Discussioncontrasting
confidence: 59%
“…Compared to other sub-Saharan countries, Ethiopia has been recently demonstrated to bear a considerable burden of neglected tropical diseases, mainly attributable to leishmaniosis, trachoma, podoconiosis, ascariasis and leprosy [31]. Despite giardiasis, cryptosporidiosis and amoebiasis are also known to be widespread in the country [7,8,[10][11][12]16], including the Oromia Region [9,14,15], the public health and development impact of these enteric illnesses remains largely unknown. To gain insight and improve our understating on the epidemiological situation of G. duodenalis, Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%